Option Backdating and Board Interlocks - Bizjak, John; Lemmon, Michael; Whitby, Ryan (Review of Financial Studies, 2009)
We examine the role of board connections in explaining how the controversial practice of backdating employee stock options spread to a large number of firms across a wide range of industries. The increase in the likelihood that a firm begins to backdate stock options that can be explained by having a board member who is interlocked to a previously identified backdating firm is approximately one-third of the unconditional probability of backdating in our sample. Our analysis provides new insight into how boards function and the role that they play in providing managerial oversight and determining corporate strategy. The Author 2009. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oxfordjournals.org., Oxford University Press.